Numerical simulation and experimental investigation of ultrasonic guided wave propagation in pipes with defects - Ghavamian, Aidin (2018)
In-service pipelines are elongated structures which are widely employed to transport various types of liquid components and products in the gas, oil, and petrochemical industries. However, as pipelines age and encounter a number of changing environmental circumstances, defects such as corrosion and cracks can usually develop and affect the working condition of in-service pipelines. Defective pipelines can result in casualties, damage to the environment, litigation, high replacement costs, and property damage. In recent decades, ultrasonic guided waves (UGW) can detect corrosion and defects in pipes successfully, but the detection capabilities using the UGW technique are considerably affected by the complex profiles of the defects. The effects of notch depth, circumferential extent, frequency and pipe size on the reflection coefficient (RC) of the T(0,1) and L(0,2) modes were analysed numerically and experimentally. Good agreement was achieved between simulation and experimental results. The study shows that the RC of the T(0,1) mode obtained from the notches depends on the circumferential extent, notch depth and pipe size (diameter). A higher RC magnitude was obtained for 100% wall thickness notch, whereas the RC of the T(0,1) mode for 50% wall thickness notch was highly sensitive to frequency changes. Furthermore, the RC of the L(0,2) received from both notches was dependent on the notch depth and the pipe size. The effects of frequency on the RC was significant since a smaller RC magnitude was observed for the notch 50% through-wall depth than for the notch of 100% as the frequency changes. In addition, the propagation of the T(0,1) mode reflected from an axisymmetric circumferential notch (defect) with different depths and circumferential extents in steel pipes was parametrically studied using the finite element ABAQUS/Explicit software. The results show that the RC of the T(0,1) mode from the notch increases as the depth and circumferential length of the notch increase. Furthermore, the RC response is dependent on the changes in the crosssection area of the notch. The results reveal that the T(0,1) mode is sensitive to the circumferential axisymmetric defects of various depths and circumferential extents. This study also attempted to approach a basis to use the GW technique for defect sizing in different pipe sizes by obtaining the RC from notches (defects) numerically. Finally, the results showed that it is possible to detect and size of various circumferential defects in different size of pipes when the T(0,1) or L(0,2) modes were incidents using this simulation models.